Language proficiency and communication strategy preference of Asian students - Guo, Qi (2006)
To achieve comprehensibility, second language learners often make use of communication strategies. Studies revealed that there is a certain relationship between L2 learners' language proficiency and their use of communication strategies. The sample consisted of 30 Asian students studying in the Philippines. A mixed method sequential exploratory research design was adopted in this study. It was found that the communication strategies often used by all the participants are repitition, restructuring, approximation, appeal for assisstance, and circumlocution. Recommendations have been made in three aspects: theory, practice, and future research.
Thesis (M.A. Language Education)--University of the Philippines, Diliman.
Keywords: English language -- Study and teaching -- Foreign speakers; Asian students -- Philippines; English language -- Ability testing -- Philippines